2017
DOI: 10.1590/1980-5918.030.s01.ao20
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic changes and exercise capacity in patients with adolescent idiopathic scoliosis

Abstract: Introduction: The spine deformity due to adolescent idiopathic scoliosis (AIS) generates respiratory mechanical limitations that may reduce the physical activity performance. Objective: To evaluate the thoracic deformity, exercise capacity and lung function in AIS patients comparing to healthy adolescentes. Besides investigating associations between thoracic deformity and exercise capacity in AIS patients. Methods: Thirty-two AIS patients and 22 healthy adolescents underwent chest wall evaluation by photogramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The use of photogrammetry for postural evaluation is already well established in scientific research and clinical practice [13][14][15][16]. In recent years, this resource has also been used for rib cage evaluation [17][18] and increasingly for the assessment of thoracoabdominal mobility in children [19], newborns [20] and adults [21], in populations ranging from athletes [21] to individuals with respiratory diseases [22][23]. However, there has been no other study using this technique to assess thoracoabdominal mobility in children with CF.…”
Section: Introductionmentioning
confidence: 99%
“…The use of photogrammetry for postural evaluation is already well established in scientific research and clinical practice [13][14][15][16]. In recent years, this resource has also been used for rib cage evaluation [17][18] and increasingly for the assessment of thoracoabdominal mobility in children [19], newborns [20] and adults [21], in populations ranging from athletes [21] to individuals with respiratory diseases [22][23]. However, there has been no other study using this technique to assess thoracoabdominal mobility in children with CF.…”
Section: Introductionmentioning
confidence: 99%
“…In the first, the authors showed distinct angles with excellent intraobserver and interobserver reproducibility and good accuracy to detect thoracic alterations in children born prematurely. The others studies showed the correlation between exercise capacity, lung function, and chest wall geometry 10,16,17 .…”
Section: Introductionmentioning
confidence: 97%
“…Despite the increasing number of studies using photogrammetry 10,[12][13][14][15][16][17] , there is still no standardization on angles used to verify chest wall changes.…”
Section: Introductionmentioning
confidence: 99%